A Taxonomy of Financial Crisis Resolution Mechanisms: Cross-Country Experience - Calomiris, Charles W; Klingebiel, Daniela; Laeven, Luc (World Bank, Washington, D.C., 2013)
The goals of financial restructuring are to re-establish the creditor-debtor relationships upon which the economy depends for an efficient allocation of capital, and to accomplish that objective at minimal cost. Costs include direct costs to taxpayers of financial assistance and the indirect costs to the economy that result from misallocations of capital and incentive problems resulting from the restructuring. The authors review cases in which countries employed alternative mechanisms to restructure their financial and corporate sectors. Countries typically apply a combination of tools, including decentralized, market-based mechanisms and government-managed programs. Market-based strategies seek to strengthen the capital base of financial institutions and/or borrowers to enable them to renegotiate debt and resume new credit supply. Government-led restructuring strategies often include the establishment of an entity to which non-performing loans are transferred or the government's sale of financial institutions, sometimes to foreign entrants. Market-based mechanisms can, in principle, resolve coordination problems countries face in the wake of massive debtor and creditor insolvency, with acceptably low direct and indirect costs, particularly when those mechanisms are effective in achieving the desirable objective of selectivity. However, these mechanisms depend for their success on an efficient judicial system, a credible supervisory framework and authority with sufficient enforcement capacity, and a lack of corruption in implementation. Government-managed programs may not seem to depend as much on efficient legal and supervisory institutions for their success, but in fact these approaches, in particular the transfer of assets to government-owned asset management companies, also depend on effective legal, regulatory, and political institutions for their success. Further, a lack of attention to incentive problems when designing specific rules governing financial assistance can aggravate moral hazard problems, unnecessarily raising the costs of resolution. These results suggest that policymakers in emerging market economies with weak institutions should not expect to achieve the same level of success in financial restructuring as other countries, and that they should design resolution mechanisms accordingly. Despite the theoretical attraction of some complex market-based mechanisms, simpler resolution mechanisms that afford quick resolution of outstanding debts, that improve financial system competitiveness, and that offer little discretion to governments are most effective.